Giant Angular Nernst Effect in the Organic Metal α-(BEDT-TTF)2KHg(SCN)4 - Krstovska, Danica; Choi, Eun Sang; Steven, Eden (MDPI AG, 2023)
We have detected a large Nernst effect in the charge density wave state of the multiband organic metal α-(BEDT-TTF)2KHg(SCN)4. We find that apart from the phonon drag effect, the energy relaxation processes that govern the electron–phonon interactions and the momentum relaxation processes that determine the mobility of the q1D charge carriers have a significant role in observing the large Nernst signal in the CDW state in this organic metal. The emphasised momentum relaxation dynamics in the low field CDW state (CDW0) is a clear indicator of the presence of a significant carrier mobility that might be the main source for observation of the largest Nernst signal. The momentum relaxation is absent with increasing angle and magnetic field, i.e., in the high-field CDW state (CDWx) as evident from the much smaller Nernst effect amplitude in this state. In this case, only the phonon drag effect and electron–phonon interactions are contributing to the transverse thermoelectric signal. Our findings advance and change previous observations on the complex properties of this organic metal.